The influence of the police professional code of ethics, and remuneation on the performance of polri members in garut police - Syaifuddin Syaifuddin (Jurnal Mantik, 2023)
The essence of this research is how the Police Professional Code of Ethics and Remuneration can improve the Performance of Police Members at the Garut Police. The aim of this research is to determine the influence of the National Police's professional code of ethics and remuneration on the performance of National Police members at the Garut Police. This research uses quantitative research methods with a descriptive approach. The results of the research show that the magnitude of the influence of the Police Professional Code of Ethics and Remuneration on the Performance of Police Officers at the Garut Police is 85.6% or has a very strong influence, the remaining 14.4% is influenced by other factors not examined in this case. From the research results, it was concluded that the Polri professional code of ethics has been regulated in police regulations, the remuneration value is still considered very small and does not meet the needs of Polri members, so that the performance of Polri members has not yet reached the optimal point. Based on the research results, researchers concluded that leaders have a strong commitment to implementing the Professional Code of Ethics for Police Members, supported by ideal remuneration values.